Breast Implant Illness Syndrome (BII): statistical analysis involving 167 women (Research, Society and Development, 2023)
The Breast Implant Illness Syndrome (BII), popularly known as the silicone disease, consists of a series of disabling and distressing physical and psychological symptoms. Thus, the objectives of the present study are to analyze whether the women with the prosthesis had any symptoms characteristic of the BII syndrome, whether they had a family history of any symptom characteristic of the BII before the prosthesis was placed, in addition to investigating the existence of an association between range age, surgical technique used to place the prosthesis and its volume, with sociodemographic variables and whether patients were informed that they could develop BII. This is a primary cross-sectional, qualitative, and descriptive study with a sample of 167 women. The result was that there was statistical significance between the technique used (p= 0.024) with the variable reason for surgery, between the volume of the prosthesis (p=0.024) and another statistical significance was found in the question if she was informed that she could develop BII (p =0.008) with the age group variable. To conclude, it was observed that in the family history there were some characteristic symptoms of BII, regarding the volume of the prosthesis, it was noted that women with larger volumes underwent surgery for aesthetic reasons, the subglandular surgical technique was the most used in women and the reason was illness. The age group that most underwent surgery was adults and adolescents were the age group more informed about the possibility of developing BII than adults.